Intercommunal justice in the Aymara communities of the southern Andean region: (Second part) - Peña Jumpa, Antonio (2002)
In the intercommunal conflict resolution procedure, we can appreciate the use of the same instruments of the resolution procedures applied to intracommunal conflicts in the study communities. Particularly noteworthy in this action is the presence of family honor and collective being as two fundamental principles that promote the resolution procedure.